EXPRESSION OF SEED VIGOR AND INITIAL GROWTH OF RED CLOVER UNDER FUNGICIDE INFLUENCE (Colloquium Agrariae. ISSN: 1809-8215, 2019)
The objective of this study was to evaluate the expression of seeds vigor and physiological performance of initial growth of red clover plants under the influence of fungicide doses of carboxin + thiram. Three lots of seeds were used (high; medium and low vigor) treated with 0; 150; 250 fungicide doses and 350 mL i.a./100 kg of seeds. Germination, first count, emergence and speed index of seedling emergence, length and dry matter of shoot and root, leaf area and shoot/root ratio were evaluated. The experimental design was completely randomized in a factorial 3 x 3 (three lots - high, medium and low vigor x three fungicide doses of carboxin + thiram). Data were submitted to analysis of variance and if significant at 5% probability, adjusted for orthogonal polynomials. According to the data observed in Figures 1, 2 and 3, it was possible to observe that there were significant differences for the means of the variables germination, first germination count, emergency, emergency speed index, shoot length, root length, aerial part dry mass, root dry mass, leaf area, leaf area ratio and shoot and root ratio. The fungicide doses of 150 mL to 350 mL i.a./100 kg of seeds result in greater seedling emergence, higher leaf area ratio and increased shoot/root ratio in plants from lots of medium vigor seeds. The fungicide consisted of carboxin + thiram enhances the expression of seed vigor and physiological performance of plant growth derived from lots of medium vigor seeds.